Performance of Microalgae Consortia in Palm Oil Mill Effluent Remediation: An Eco-Friendly Strategy - Andin Vita Amalia; Tri Retnaningsih Soeprobowati; Marcelinus Christwardana (Jurnal Pendidikan IPA Indonesia, 2026)
Palm oil production continues to grow in line with global market demand; however, production waste is also expected to increase. The treatment of Palm Oil Mill Effluent (POME) remains a critical environmental challenge due to its high organic load and complex pollutant composition, thereby requiring serious management. This study investigates the potential of four microalgal consortia in remediating POME. A quantitative experimental approach was employed to evaluate the efficiency of the microalgae consortium exposed to different POME concentrations (25%, 50%, and 75%) over 14 days. The results revealed that the three-species consortium CNT (Chlorella vulgaris, Nannochloropsis oculata, and Tetraselmis chuii) exhibited superior performance in reducing COD, BOD, and TSS, with removal efficiencies of 77.55%, 72.73%, and 49.7%, respectively, compared to the two-species consortium. The optimal physicochemical parameters supporting CNT growth were recorded at pH 9.19-9.6, 29.1-30.6 °C, and adaptive salinity up to 41 ppt. The biomass yield of the CNT consortium (3.862 g L⁻¹ at 25% POME) was lower than that of NT (4.671 g L⁻¹ at 25% POME), indicating that CNT allocated more energy to detoxifying and remediating POME than to biomass accumulation. Future research should focus on optimizing response surface methodology and scaling up photobioreactor systems through metagenomic and transcriptomic analyses to simultaneously maximize remediation efficiency and biomass productivity of the CNT consortium. These findings provide strategic opportunities to harness polyculture microalgae consortium as a sustainable, scalable, and economically viable technology for POME remediation.